2012
DOI: 10.1016/j.psychres.2011.08.014
|View full text |Cite|
|
Sign up to set email alerts
|

Inflammatory markers in antipsychotic-naïve patients with nonaffective psychosis and deficit vs. nondeficit features

Abstract: Newly diagnosed, antipsychotic-naïve patients with nonaffective psychosis appear to have increases in pro-inflammatory cytokines. Patients characterized by primary, enduring negative symptoms (deficit symptoms) differ from patients without such features with regard to course of illness, treatment response, risk factors and metabolic disturbances. We hypothesized that they would also differ on the inflammatory markers, interleukin-6 (IL6) and C-reactive protein (CRP) concentrations. Newly diagnosed, antipsychot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 49 publications
13
32
0
Order By: Relevance
“…Several studies have explored socio-demographic characteristics Messias et al, 2004), risk factors (Kirkpatrick et al, 2000a), clinical outcome (Carpenter, 1994;Tek et al, 2001), response to treatment (Kirkpatrick et al, 2000b) and neurobiological features Ross et al, 1997;Waltrip et al, 1997;Hong et al, 2005) associated with SZD. Some studies have demonstrated double dissociations (SZD patients impaired on measure A but not B; SZND patients impaired on measure B but not A) in metabolic measures (Garcia-Rizo et al, 2012), season of birth (Messias et al, 2004), and electrophysiological variables (Mucci et al, 2007). These studies are consistent with the concept that SDZ is a separate disorder within the syndrome of schizophrenia.…”
Section: Introductionsupporting
confidence: 60%
“…Several studies have explored socio-demographic characteristics Messias et al, 2004), risk factors (Kirkpatrick et al, 2000a), clinical outcome (Carpenter, 1994;Tek et al, 2001), response to treatment (Kirkpatrick et al, 2000b) and neurobiological features Ross et al, 1997;Waltrip et al, 1997;Hong et al, 2005) associated with SZD. Some studies have demonstrated double dissociations (SZD patients impaired on measure A but not B; SZND patients impaired on measure B but not A) in metabolic measures (Garcia-Rizo et al, 2012), season of birth (Messias et al, 2004), and electrophysiological variables (Mucci et al, 2007). These studies are consistent with the concept that SDZ is a separate disorder within the syndrome of schizophrenia.…”
Section: Introductionsupporting
confidence: 60%
“…Consistent with this hypothesis, Garcia-Rizo et al [30] found increased inflammatory markers in a specific subsample of patients (those with deficit syndrome) when compared with other first-episode psychosis patients (see the section below for more details).…”
Section: Markers Of Inflammation In First-episode Psychosismentioning
confidence: 75%
“…The first study by Fernandez-Egea et al [21] reported both increased levels of IL-6 and increased prevalence of abnormal glucose tolerance in drug-naïve first-episode psychosis patients, supporting the co-occurrence of inflammatory and metabolic abnormalities at the onset of psychosis. A second study focussing on a sample of patients with deficit symptoms (already described above), found increased levels of inflammatory parameters but lower glucose levels at oral glucose tolerance test, suggesting a dissociation between inflammation and glucose intolerance in this particular group of patients [30]. In the last study, we showed that first-episode psychosis patients with a history of childhood sexual abuse had significantly higher CRP levels and BMI than first-episode psychosis patients without a history of childhood abuse and healthy controls [35].…”
Section: Inflammation and Physical Health In First-episode Psychosismentioning
confidence: 99%
“…IL-6 may be the most important pro-inflammatory cytokine implicated in the microglial activity inhibiting adult neurogenesis by acting on the IL-6 receptor or on a common signal transducer in the dentate gyrus [7].Several studies suggest that microglia activation and elevated levels of proinflammatory cytokines are associated with the development of schizophrenia. Recent studies using positron emission tomography studied the role of microglia in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of IL-6 and C-reactive protein (CRP) in drug-naïve patients with psychosis have been correlated with severe negative and cognitive symptoms, poor prognosis and poor response to antipsychotic medications [7].More recently, IL-17 has been implicated in the pathophysiology of autoimmune diseases of the CNS. Borocvanin et al reported low levels of IL-17 and high levels of IL-4 and TGF-β2 in drug-naïve patients with psychosis as well as in patients in relapse, assuming that TGF-β2, whose increased levels are correlated with the onset and the relapse of schizophrenia, is a reliable biomarker for the early detection of the onset and the relapses of the disorder [2].…”
Section: Introductionmentioning
confidence: 99%